The Effect of Sales Growth, Profitability, Leverage and Corporate Governance on Financial Distress - Kholifah, Reza; Uzliawati, Lia; Lestari, Tri (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine the effect of Sales Growth, Profitability, Leverage and Corporate Governance on Financial Distress. The research population includes service companies in the infrastructure, utilities and transportation sectors listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample selection method used was purposive sampling and 20 companies were selected with a total sample of 80 research data. The analysis technique used is logistic regression using SPSS 26 software. The results of this study indicate that sales growth, profitability, leverage and corporate governance which are proxied by institutional ownership and managerial ownership have a simultaneous influence on financial distress. while partially, sales growth, leverage and corporate governance have no effect on financial distress, and profitability has a significant influence on financial distress. Keywords: Sales Growth, Profitability, Leverage, Corporate Governance, Financial Distress